Innovative Model for Material Selection Within the Automotive Lightweight Eco-Design Field - Edoardo Risaliti; Arcidiacono Gabriele; Francesco Del Pero; Paolo Citti (Engineering Proceedings)
This paper presents an innovative integrated Ashby-VIKOR model for material selection when dealing with the re-design of automotive components under a wide-spectrum range of both sustainability and design aspects. The conceived approach combines the Ashby method, which assesses mechanical properties and costs, with the VIKOR multi-criteria decision analysis, including a comprehensive model functional to assess the environmental impact of the considered automotive assets. This study also incorporates the implementation of the methodology to a literature case study (engine bracket for a C-class electric vehicle) to evaluate the robustness of the approach under varying different boundary conditions of the analysis. The results show the usefulness of the method in assessing new lightweight design solutions under an integrated structural integrity/sustainability point of view. In particular, the outcomes of the case study analysis show that significant improvements are offered by the lightweight alternative both in terms of component weight, cost efficiency and carbon footprint, identifying low-alloy steels and aluminum composites as optimal materials for this specific application.